The meaning of religion/religiosity for the elderly - Ana Luíza Barreto de Oliveira; Tânia Maria de Oliva Menezes
ABSTRACT Objective: To understand the meaning of religion/religiosity for the elderly. Method: A qualitative, phenomenological study, based on Martin Heidegger. Thirteen older women registered in an Urban Social Center of Salvador, Bahia, Brazil aged between 60 and 84 years participated in the study. The collection of testimonies was carried out from November 2013 to May 2014 through phenomenological interviews. Results: Hermeneutics has unveiled the unit of meaning: Meanings of religion/religiosity in the daily life of the elderly. Religion/religiosity offers comfort and well-being to the elderly person, helping to overcome changes arising from the aging process. Final considerations: The nurse, while providing care, should expand his/her vision in relation to the subjectivity of the elderly, in order to understand that religion/religiosity gives meaning to their existence.